FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KETIDAKBERHASILAN PEMBERIAN ASI EKSKLUSIF DI KECAMATAN BAITUSSALAM KABUPATEN ACEH BESAR TAHUN 2023 - Simeulue, Ridha Juita; Susanti, Dewina; Efriana, Cut; Saudah, Saudah; Ristiani, Fina; Marhaliza, Putri (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2023)
Based on WHO (World Health Organization) data in 2021, it is reported that the global exclusive breastfeeding coverage is around 44% of infants aged 0-6 months worldwide who are exclusively breastfed during the 2015-2021 period. This has not yet reached the target for exclusive breastfeeding coverage in the world, which is 50%. Low exclusive breastfeeding will have an impact on the quality and livability of the next generation. The purpose of the study was to determine the factors associated with the failure of exclusive breastfeeding in Baitussalam District, Aceh Besar Regency in 2023. Research Methods This type of research is an analytical survey research using a Cross Sectional approach, Cluster random sampling technique with a sample size of 66 people. The research instrument was a questionnaire. Data analysis using univariate and bivariate analysis with the SPSS statistical program. The results of statistical tests with the Chi-square test showed a p-value of 0.020 <0.05, so there was a mother's age on the failure of exclusive breastfeeding in Baitussalam District, Aceh Besar Regency in 2023. The statistical test results with the Chi-square test showed a p-value of 0.052 <0.05, so there was a relationship between maternal knowledge of breastfeeding techniques on the failure of exclusive breastfeeding in Baitussalam District, Aceh Besar Regency in 2023. The statistical test results with the Chi-square test showed a p-value of 0.032 <0.05, so there was a relationship between maternal employment and the failure of exclusive breastfeeding in Baitussalam District, Aceh Besar Regency in 2023. The statistical test results with the Chi-square test showed a p-value of 0.031 <0.05, so there was a relationship between breastfeeding experience and the failure of exclusive breastfeeding in Baitussalam District, Aceh Besar Regency in 2023. The statistical test results with the Chi-square test showed a p-value of 0.069 <0.05, so there was no relationship between the support of health workers on the failure of exclusive breastfeeding in Baitussalam District, Aceh Besar Regency in 2023. The statistical test results with the Chi-square test showed a p-value of 0.050 <0.05, so there was a relationship between family support for the failure of exclusive breastfeeding in Baitussalam District, Aceh Besar Regency in 2023. Conclusion There is a relationship between maternal age, maternal knowledge of breastfeeding techniques, maternal employment, breastfeeding experience, family support on the failure of exclusive breastfeeding. There is no relationship between the support of health workers and the failure of exclusive breastfeeding.